S13 Manchester lung screening, targeting high-risk individuals in deprived areas of the community. (15th November 2017) - Balata, H; Crosbie, P; Evison, M; Yarnell, L; Threlfall, A; Barber, P; Tonge, J; Booton, R
Abstract : Background: Lung cancer (LC) is the commonest cause of cancer-related death in the world. Screening with low-dose computer tomography (LDCT) had been shown to reduce LC specific and all-cause mortality. Benefit is greatest in those at highest risk, such as current smokers from areas of high socio-economic deprivation, yet participation in these 'hard-to-reach' populations remains a challenge. The aim of this NHS implementation project was to assess LC screening within the community in deprived areas. Methods: Ever smokers, aged 55–74, registered at 14 participating general practitioner (GP) practices in deprived areas of Manchester were invited to attend and have a free 'Lung Health Check' (LHC) in a mobile unit located at their local shopping centres. Lung cancer risk score (PLCOM2012 ), respiratory symptoms and spirometry were assessed as part of the LHC. Those at high risk of LC, i.e., 6 year lung cancer risk ≥1.51%, were offered immediate LDCT in a co-located mobile CT scanner. All active smokers were provided with smoking cessation advice. Results: The maximum available capacity of the service was filled within days of going live. A total of 2541 individuals attended for a LHC and consented to data analysis. The mean age was 64.1±5.5 and 51.0% (n=1, 296) were female. 74.5% (n=1, 893) of participants were ranked in the lowest quintile of deprivation in England. The majority of individuals had left school by the age of 16 (n=2, 078; 81.8%), most without gaining any 'O' levels (n=1, 567; 61.7%). A significant number of participants reported a history of previous respiratory disease (n=566; 22.3%), pervious cancer (n=291; 11.5%), family history of LC (n=553; 21.8%) or asbestos exposure (n=612; 24.1%). 56.2% (n=1, 429) qualified for LDCT screening of which 52.8% were active smokers. 46 lung cancers were detected in 42 individuals, a prevalence of 3.0%, of which 80.4% were early stage (I+II). A treatment with curative intent was offered to 89.1% of screen detected cancers. Conclusion: Taking lung cancer screening into the community can identify and affect those at most risk, the so-called 'hard-to-reach' populations. This Results in a significant stage shift in screen detected lung cancers in deprived populations.